An update on expanding HIV preexposure prophylaxis. Issue 2 (February 2023) - Baker, Jonathan; Rolls, Joanne
ABSTRACT: HIV continues to affect certain populations disproportionately, including sexual and gender minorities, racial/ethnic minorities, and populations with limited resources in southern US states. New CDC guidelines include a recommendation to discuss HIV preexposure prophylaxis (PrEP) with all sexually active patients, which is likely to expand use. The guidelines also include important changes in PrEP monitoring and address PrEP telehealth. The FDA approved the first non-oral PrEP, long-acting injectable cabotegravir, in late 2021. However, PrEP continues to be underused. This article describes how to better employ PrEP in light of these recent significant changes.